التصميم البيئي الملائم للأبنية الإدارية في مدينة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2016)
كان للإنسان منذ القدم باعٌ طويلٌ في تطويع الفراغاتِ المعمارية بغْيةَ انسجامها مع معطيات البيئة التي يعيش ضمنها، فحاول قدر استطاعته خلق عمارة تنسجم مع معطيات البيئة الخاصة به بكل مكوناتها المناخية والاجتماعية والاقتصادية. استمر هذا التلاؤم بين العمارة والبيئة ردحاً طويلاً من الزمن وصولاً للفترة المعاصرة في منطقتنا المحلية والتي حدثت فيها فجوة كبيرة بين العمارة والبيئة أدت إلى غياب الدراسات البيئية في الأبنية المحلية والتي انعكست بشكل سلبي على مكونات البيئة الطبيعية المحيطة وخلقت أبنية غير اقتصادية عالية الكلفة من حيث التشغيل. وعلى اعتبار أن الأبنية الإدارية إحدى أهم مكونات النسيج العمراني للمدينة كان لدراسة تطبيقات العمارة البيئية في هذه الأبنية (في حالة مدينة اللاذقية) الأهمية الكبيرة والتي دلت على أن هذه الأبنية بعيدة كل البعد عن مفاهيم العمارة البيئية وأنها تصاميم قاصرة بيئياً لا تنسجم مع معطيات البيئة المكانية لمدينة اللاذقية.هذه الفجوة بين البيئة وعمارة المبنى الإداري دعتنا إلى المناداة بضرورة الاهتمام بالعمارة البيئية والمسارعة إلى البدء بوضع الأنظمة والضوابط التي تعمل على خلق عمارة إدارية بيئية تحقق الاستدامة الاقتصادية المنشودة وتتفاعل مع البيئة الطبيعية المحيطة وتكفل حياة صحية ونفسية لمستخدميها.The human has a long history in the adaptation of architectural spaces with a view to its compatibility with the requirements of the environment in which they live, including, try as much as possible to create architecture consistent with the data environment with all its climatic, social and economic components.This mismatch between the architecture and the environment has continued for so long of time right up to contemporary period in our local area and where large gap occurred between architecture and the environment led to the absence of environmental studies in the local buildings, which reflected negatively on the natural environment surrounding components and created buildings uneconomical high cost in terms of operating .Considering that administrative buildings one of the most important urban fabric components of the city was to study the environmental architecture applications in these buildings in the case of the city of Latakia, the great importance which indicated that these buildings are far from the concepts of environmental architecture and it is limited to designs very primitive in terms of the environment and the possibilities of harmony and compatibility with Environment.This gap between the environment and building administrative building invited us to the need to call attention to environmental architecture and quickly begin to develop and controls systems that work to create an administrative building environmental sustainability and achieve the desired economic and interact with the surrounding natural environment and ensure the health and psychological life to its users.